A Systematic Review to Assess Resection Margin Status After Abdominoperineal Excision and Pelvic Exenteration for Rectal Cancer. Issue 2 (February 2017) - Simillis, Constantinos; Baird, Daniel L. H.; Kontovounisios, Christos; Pawa, Nikhil; Brown, Gina; Rasheed, Shahnawaz; Tekkis, Paris P.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to assess resection margin status and its impact on survival after abdominoperineal excision and pelvic exenteration for primary or recurrent rectal cancer. Summary of Background Data: Resection margin is important to guide therapy and to evaluate patient prognosis. Methods: A meta-analysis was performed to assess the impact of resection margin status on survival, and a regression analysis to analyze positive resection margin rates reported in the literature. Results: The analysis included 111 studies reporting on 19, 607 participants after abdominoperineal excision, and 30 studies reporting on 1326 participants after pelvic exenteration. The positive resection margin rates for abdominoperineal excision were 14.7% and 24.0% for pelvic exenteration. The overall survival and disease-free survival rates were significantly worse for patients with positive compared with negative resection margins after abdominoperineal excision [hazard ratio (HR) 2.64, P < 0.01; HR 3.70, P < 0.01, respectively] and after pelvic exenteration (HR 2.23, P < 0.01; HR 2.93, P < 0.01, respectively). For patients undergoing abdominoperineal excision with positive resection margins, the reported tumor sites were 57% anterior, 15% posterior, 10% left or right lateral, 8% circumferential, 10% unspecified. A significant decrease in positive resection margin rates was identified over time for abdominoperineal excision. Although positive resection margin rates did not significantly change with the size of the study, some small size studies reported higher than expected positive resection margin rates. Conclusions: Resection margin status influences survival and a multidisciplinary approach in experienced centers may result in reduced positive resection margins. For advanced anterior rectal cancer, posterior pelvic exenteration instead of abdominoperineal excision may improve resection margins.